Design and development of a computerized education records system. - Robinette JE; Weitzel PS (Journal of Continuing Education in Nursing)
An efficient and cost effective computerized education records system was developed to provide centralized and decentralized reports of education participation. Collaboration with a computer analyst and programmer was essential to integrate our education information database with the hospital's mainframe system.